Waste Management and Its Effects (International Journal of Food and Nutritional Sciences, 2022)
Effective waste management is required for environmental protection. Its mission is to provide hygienic, economical, and expense wastewater storage, collection, transporting, treatment, and disposal services without causing damage to the environment, ground, or water system.Our consumption habits and shifting socioeconomic situations have made sustainable waste management procedures difficult. Waste management is a multifaceted issue that necessitates the integration of technology, economics, sociocultural, and political activities. This paper aims to describe the most important features of waste management methods, as well as the interactions between the variables stated above. In addition, the paper includes some basic information on worldwide garbage creation, as well as an update on today's modern waste management technology. The interplay of the many components is emphasized. In this paper we discussed about the cycle of waste management and its preventions and uses. The future scope of this study is the basic understanding of management waste in an effective manner.